PELAKSANAAN KEWENANGAN BADAN KEHORMATAN DPRD DALAM PENEGAKAN KODE ETIK DI DPRD PROVINSI RIAU TAHUN 2019-2021 - Zulfadly Trisananda; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
DPRD members are representatives of the people in the regions who must be able to aspire to the wishes of their constituents. DPRD members, in carrying out their duties, functions, and authorities, must of course comply with all applicable regulations. However, there are various phenomena that arise related to the attitudes and behavior of DPRD members in Riau Province, such as absenteeism at DPRD meetings, improprieties that should not be carried out, and indisciplined DPRD members who are considered to have violated the code of ethics. Therefore, an honorary body was formed as a code of ethics enforcement agency tasked with maintaining the dignity, image, and credibility of the DPRD. This study aims to determine the implementation of the authority of the DPRD honorary body in enforcing the code of ethics in the DPRD Riau Province in 2019–2021. This study uses the study of authority theory, in which authority originates from attribution, delegation, and mandate. The method in this study uses descriptive research with a qualitative approach. Sources of data consist of primary data and secondary data collected through interviews and documentation. Data analysis used qualitative data analysis techniques with interactive models. The results of this study indicate that the Honorary Board of DPRD Riau Province has exercised its authority in enforcing the code of ethics. However, it is not optimal. The honorary body has more of a passive role in waiting for complaints. There are several issues that have developed in the community that are not being processed by the honorary body because no complaints have been received. Several factors impede the implementation of the authority of the honorary body, namely the colliding with the code of ethics and procedures for the honorary body, which makes the honorary body seem slow and rigid, the lack of participation from the community, and political elements because members of the honorary body are also members of the DPRD, so whether they realize it or not, there is a considerate nature among fellow DPRD members. Keywords: authority, DPRD Ethics Council, enforcement of the code of ethics